A High Precision Reconfigureable Bistatic Interferometric Radar with Integrated Six-port Receiver at 60 GHz - Völkel, Matthias; Mann, Sebastian; Frank, Martin; Weigel, Robert; Hagelauer, Amelie Marietta (2019 12th German Microwave Conference (GeMiC), 2019)
In this paper a 60GHz bistatic reconﬁgureable sixport radar for high precision measuring is presented. The frontend is designed in a substrate-integrated waveguide technology including coupler, attenuator and transmission lines. The core of the front-end is a integrated six-port receiver MMIC including the passive six-port structure, a LNA and four detectors. It has been designed using a 0.13µm SiGe BiCMOS process. A BGT60, stabilized by a PLL-circuit, generates the transmit signal for vivaldi antennas. The system includes also a baseband circuit with adjustable differential ampliﬁer, 24bit@52kSa/s ADC converter for signal sampling and DAC converter for gain and attenuation tuning. Furthermore, the stacked system is directly connected to a FPGA board. A full NIOS2 system is set up to control the radar and send the collected data via ethernet to the PC. C++ software is written to conﬁgure the system in an easy comfortable way and to visualize the measured data. Measurements show, that the radar works in a range up to ﬁve meter. The maximum distance deviation at 1m is 30µm and the standard deviation is 12.6µm.<br
Keywords: bistatic; FPGA; integrated receiver; interferometry; millimeter wave circuits; radar systems; six-port; substrateintegrated waveguide (SIW)